Language alternation, language choice and language encounter in international tertiary education - Haberland, Hartmut; Lonsmann, Dorte; Preisler, Bent 1945- (Multilingual education, 2013)
Reflecting the increased use of English as lingua franca in today's university education, this volume maps the interplay and competition between English and other tongues in a learning community that in practice is not only bilingual but multilingual. The volume includes case studies from Japan, Australia, South Africa, Germany, Catalonia, China, Denmark and Sweden, analysing a range of issues such as the conflict between the students' native languages and English, the reality of parallel teaching in English as well as in the local language, and classrooms that are nominally English-speaking but multilingual in practice. The book assesses the factors common to successful bilingual learners, and provides university administrators, policy makers and teachers around the world with a much-needed commentary on the challenges they face in increasingly multilingual surroundings characterized by a heterogeneous student population.